The Occurrence and Relationship of Postoperative Seizure and de novo Epilepsy after Craniotomy Surgery: A Retrospective Single-Center Cohort Study - Horiuchi, Sayaka; Kanaya, Kohei; Horiuchi, Tetsuyoshi (Frontiers in Surgery, 2022)
Objective: Postoperative seizures and epilepsy are common complications of craniotomy. In this study, we aimed to investigate the characteristics of seizures and epilepsy after craniotomy. Methods: A total of 293 consecutive craniotomy surgeries were analyzed. Infratentorial surgeries, epilepsy surgeries, surgeries using the same approach conducted for the same patients, and the cases with incomplete clinical data were excluded. A total of 211 surgeries were included in this study. We evaluated the following clinical characteristics in all patients: sex, age, preoperative epilepsy, use of preoperative antiseizure medication (ASM), indication for operation, early postoperative seizure (EPS), delayed postoperative seizure (DPS), and postoperative de novo epilepsy. The day of onset of EPSs was defined as within 7 days post-surgery, and the day of onset of DPSs was defined as later than 7 days and less than 60 days post-surgery. Results: Twenty-eight patients were previously diagnosed with epilepsy. Nine patients had EPSs (4.3%), and 10 patients had DPSs (4.7%). Seven cases of EPSs and six cases of DPSs were observed in 183 patients without previous epilepsy (3.8% and 3.3%, respectively). Three of the seven patients with EPSs (42.9%) and all six patients with DPSs (100%) developed de novo epilepsy. Postoperative de novo epilepsy was observed in 9 (4.9%) of the 183 patients without epilepsy. EPSs and DPSs were significant risk factors for epilepsy (p < 0.01). The odds ratios of EPSs and DPSs for the development of epilepsy were 12.71 (95% confidence interval [CI]: 3.94-112.80; p < 0.01) and 22.88 (95% CI: 5.38-55.72; p < 0.01), respectively. ASM was administered prophylactically to 51 patients. The prophylactic use of ASMs did not prevent EPSs or postoperative de novo epilepsy. Conclusion: EPSs and DPSs occurred in 4.3% and 4.7% of the patients, respectively, after craniotomy. Postoperative de novo epilepsy occurred in 4.9% of patients. This study revealed that EPSs and DPSs were risk factors for de novo epilepsy. Previous epilepsy was not a significant risk factor for EPSs. The prophylactic use of ASMs did not prevent EPSs or de novo epilepsy.